Influence of the mean airway pressure trajectory on the mortality and AKI occurrence in septic shock patients with mechanical ventilation: insights from the MIMIC-IV database - Dong, Yukang; Yang, Changyan; Sun, Run; Fu, Jiangquan; Huang, Rui; Yuan, Jia; Wang, Ying; Wang, Jinni; Shen, Feng (Frontiers in Medicine, 2025)
BackgroundMean airway pressure (Pmean) is a known prognostic marker for mortality and adverse outcomes in mechanically ventilated patients. However, most previous studies have relied on static measurements, leaving the impact of Pmean trajectory on clinical outcomes in septic shock patients unclear. This study aimed to investigate the effect of Pmean trajectory on survival rates and acute kidney injury (AKI) incidence in septic shock patients undergoing mechanical ventilation (MV).MethodsA retrospective cohort study was implemented utilizing sepsis patient data from the MIMIC-IV database. Group-based trajectory modeling (GBTM) was applied to identify distinct Pmean trajectory groups among septic shock patients. Cox proportional hazards and logistic regression models were utilized to analyze associations between Pmean trajectory and both mortality and AKI incidence. A causal mediation analysis evaluated the intermediary effect of cumulative fluid balance over the first 72 h post-ICU admission.ResultsA total of 956 eligible patients were included. Based on model fitting criteria, five distinct Pmean trajectory groups were identified: group 1 (low-stable), group 2 (high-descend), group 3 (medium-ascend), group 4 (high-stable), and group 5 (higher-stable). Compared to the low-stable trajectory (group 1), trajectories in groups 3, 4, and 5 were associated with significantly higher 30-day mortality risks (HR = 1.40, 95% CI = 1.03–1.88; HR = 1.47, 95% CI = 1.01–2.13; HR = 2.54, 95% CI = 1.53–4.2, respectively), while group 2 exhibited similar mortality rates to group 1 (HR = 0.88, 95% CI = 0.60–1.30). Logistic regression analyses revealed that groups 3, 4, and 5 were also significant risk factors for AKI occurrence (p < 0.05), with group 1 as the reference. Mediation analysis revealed that 20.5% (95% CI = 0.106–0.40) of the Pmean trajectory effect on AKI occurrence was mediated through cumulative fluid balance.ConclusionPmean trajectories were strongly associated with mortality and AKI incidence in septic shock patients receiving MV.